2022
DOI: 10.1002/jcla.24609
|View full text |Cite
|
Sign up to set email alerts
|

The intercorrelation among CCT6A, CDC20, CCNB1, and PLK1 expressions and their clinical value in papillary thyroid carcinoma prognostication

Abstract: Background CCT6A promotes several carcinomas' growth and invasion in multiple ways, and it relates to CCNB1 and PLK1 through its interaction with CDC20 via protein–protein interaction bioinformatics. This study aimed to explore the intercorrelation among CCT6A, CDC20, CCNB1, and PLK1, and their association with tumor features and prognosis in papillary thyroid carcinoma (PTC) patients. Methods CCT6A, CDC20, CCNB1, and PLK1 expressions in 186 tumor and 30 non‐tumor speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…CCT6A and CDC20 are overexpressed in various types of cancer (16,27,(29)(30)(31)(32), and a previous study reported that CCT6A is positively associated with CDC20 in patients with papillary thyroid carcinoma (16). However, the dysregulation and intercorrelation of CCT6A and CDC20 in patients with osteosarcoma still needs to be explored.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…CCT6A and CDC20 are overexpressed in various types of cancer (16,27,(29)(30)(31)(32), and a previous study reported that CCT6A is positively associated with CDC20 in patients with papillary thyroid carcinoma (16). However, the dysregulation and intercorrelation of CCT6A and CDC20 in patients with osteosarcoma still needs to be explored.…”
Section: Discussionmentioning
confidence: 98%
“…Chaperonin-containing tailless complex polypeptide 1 subunit 6A (CCT6A) is a recently discovered oncogene, which promotes cancer progression by facilitating the proliferation, invasiveness and stemness and of tumor cells (10)(11)(12)(13). In addition, it exhibits potency as a prognostic marker in numerous types of cancer, such as lung cancer, gastric cancer and papillary thyroid carcinoma (14)(15)(16). Notably, CCT6A interacts with cell division cycle 20 (CDC20), as shown by the STRING database (https://cn.string-db.org/) and further validated by a previous study in papillary thyroid carcinoma cancer tissue (16).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two senior pathologists performed double-blind evaluations by examining the sections under a light microscope. According to a previous study (16), 10 high-power fields were randomly selected from each section. A semi-quantitative score based on the intensity of positively stained cells and the staining area was used to evaluate the results of IHC; the comprehensive score of staining intensity was multiplied by the staining area.…”
Section: Gipc2 Expression Analysesmentioning
confidence: 99%